A study on factors affecting employee engagement among Generation Y in Klang Valley / Muhammad Azlan Ramli and Nur Amira Mesran @ Mahmood - Ramli, Muhammad Azlan; Mesran@Mahmood, Nur Amira (Faculty of Business and Management, 2014)
Employee engagement is very important in organization because engagement will help organization achieve the mission. But many current organizations have failed to engage a workforce, in order to build a competitive and sustaining business model that honors their most valuable asset, the people especially among Generation Y. In order to make organization have effective and efficient in production, the right action might be taken to bridge the gaps before it is going to be large issues. Thus this study is to examine the factors affecting employees’ engagement among Generation Y in Klang Valley. This study has been conducted within Klang Valley that involves 205 respondents of workers. Result of this study shows that there is a significant relationship between feedback, personal growth and development, and personal expression and employee engagement. The recommendation for all objectives and future research also been conducted by researchers in this report.